Investigate of turbo-compressors with general impeller for engines and power plants - Владимир Анатольевич Шкабура (National Aerospace University «Kharkiv Aviation Institute», 2021)
The article deals with the working processes in flowing part of the turbo-compressors with general impeller (TCG) and with two schemes of the flows. The work studies the features of the TCG operation with two schemes of the flows and the gas-dynamic calculation theory development of their flow parts for use in engines and power plants. The tasks to be solved are to investigate two schemes of the flows in the interscapular space of the impeller – direct-flow and counter-flow. If the gas and air flow directions coincide concerning the axis of rotation of the impeller, then the flow pattern in the TCG is direct-flow, with the opposite movement of flows – is counter-flow. The solution to this problem was performed using the developed methods of gas-dynamic calculation of the TCG flow parts. Conclusions. The scientific novelty of the results obtained is as follows: parameters that significantly affect the efficiency of the turbine and compressor parts of the TCG were established and the formula in the form of a general criterion ratio was calculated. The dependence of the correction factor is determined, which considers the effect of the ratio of the impeller width on the average diameter of the working channel of the RK in the compressor section and the turbine section of the TCG. The article contains formulas, with correction factors, for calculating the power factor in the compressor section and the load factor in the turbine section. If the ratio of the grating width to the average diameter of the working channel is overestimated, it is necessary to supplement the formulas with a correction factor that considers the effect of this ratio. Studies have determined that switching from one mode of operation to another – in a certain section of the impeller, accelerates the flow to the required speed. It is especially evident in the compressor working channel of the TCG with a counter-flow pattern. In the turbine section, the gas flow acceleration time does not depend on the flow pattern – the flow is active and accelerates to the required speed in the nozzle apparatus. The given formulas allow calculating the power of the turbine and compressor parts of the impeller to perform an enlarged gas-dynamic calculation of TCG. Studies have determined that TCG can be used in gas turbine engines and the pressurization system of an internal combustion engine.